Optical Receiver for Optical Time Domain Reflectometer - Charlamov, J.; Navickas, R.; Baskys, A.; Barzdenas, V.; Nickelson, L. (Elektronika ir Elektrotechnika, 2012)
In this paper we analyze an optical receiver (OR) for the optical time domain reflectometer (OTDR). Using optical receiver’s model, which consists of shunt-shunt feedback transimpedance amplifier (TIA) and InGaAs avalanche photodiode (APD), we discuss and give equations for all important noise sources, which are amplifiers input transistor channel thermal and flicker noises, avalanche photodiode noise and feedback resistors noise. Than in terms of OTDR parameters, we explain the need of TIA variable gain, define the range of bandwidths, and introduce optimal values for OR dynamic range, APD multiplication and feedback resistance. Using these values we give an OR reference design and analyze received results. DOI: http://dx.doi.org/10.5755/j01.eee.18.8.2624